The impact of dietary changes among the Inuit of Nunavik (Canada) : a socioeconomic assessment of possible public health recommendations dealing with food contamination - Duhaime, Gérard; Chabot, Marcelle; Fréchette, Pierre; Robichaud, Véronique; Proulx, Solange (Risk Analysis, 2024)
Inuit populations meet a large portion of their food needs by eating country food in which pollutants are concentrated. Despite the fact that they contain pollutants, the consumption of country food has many health, social, economic, and cultural benefits. A risk determination process was set up in order to help regional health authorities of Nunavik to deal with this particular issue. Based on Nunavik health authorities' objectives to encourage the region's inhabitants to change their dietary habits, and on both the risks and the benefits of eating country food, several management options were developed. The options aimed at reducing exposure to contaminants by either substituting certain foods with others that have a lower contaminant content or by store-bought foods. This article aims at assessing the potential economic impact of these risk management options before being implemented. Relevant economic data (aggregate income and monetary outlays for the purchase of food and equipment required for food production by households) were collected and identified to serve as a backdrop for the various replacement scenarios. Results show that household budgets, and the regional economy, are not significantly affected by the replacement of contaminated foods with the purchase of store-bought meat, and even less so if the solution involves replacing contaminated foods with other types of game hunted in the region. When financial support is provided by the state, the households can even gain some monetary benefits. Results show that public health authorities' recommended changes to dietary habits among the Inuit of Nunavik would not necessarily involve economic constraints for Inuit households.